Requirements for Determining Recidivist Status in Juvenile Offenders under Law No. 11 of 2012 on the Juvenile Criminal Justice System: A Contemporary Legal Perspective - Chicillia Sri Servanda; Rugun Romaida Hutabarat (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The phenomenon of juvenile recidivism presents significant legal challenges due to the absence of explicit provisions governing the criteria, indicators, and legal consequences of recidivist status for children under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This regulatory gap generates legal uncertainty and creates a tension between the imperative of law enforcement and the protection of children’s rights. This study aims to examine the requirements for determining juvenile recidivist status within the Indonesian criminal law system and to analyze judicial considerations of reoffending in Decision Number 17/Pid.Sus-Anak/2025/PN Jkt.Pst. Employing a normative legal research method, the study adopts statutory, conceptual, and case-based approaches, supported by qualitative, descriptive, and prescriptive analysis. The findings indicate that the regulation of juvenile recidivism remains characterized by a normative vacuum, thereby rendering its implementation highly dependent on judicial interpretation. The examined decision demonstrates that a developmental approach continues to be prioritized through placement in the Child Special Development Institution (LPKA) as a mechanism for child protection and rehabilitation.